Answers

The Brainliest Answer!
  • Brainly User
2014-09-06T13:32:32+05:30
3a²-4b²+5ab-x(let)=-a²-b²+6ab
Now, we will transpose, x on the right side and -a²-b²+6ab on the left side.
We will get=  3a²-4b²+5ab+a²-b²+6ab=x
3a²+a²=4a²
-4b²-b²=-5b²
5ab+6ab=11abSo, the answer is4a²-5b²+11ab



2 5 2
2014-09-07T04:37:00+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Let the expression to be subtracted be equal to X. It contains terms a², b², and ab.

3 a^2 - 4 b^2 + 5 a b - X = - a^2 - b^2 + 6 a b \\

Take X to the right side, and Bring the expression on the right to the left side of equal to.

3 a^2 - 4 b^2 + 5 a b + a^2 + b^2 - 6 a b = X \\

Add the similar terms

(3+1)a^2 + (-4+1)b^2 + (5-6) ab = X \\ \\ 4 a^2 -3b^2 -ab = X, OR,\ \ \ \ \ \  X = 4a^2 - 3 b^2 - ab \\

0